2021
DOI: 10.3389/fonc.2021.706141
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrosis-Targeted Collagen/Integrins Gene Profile Predicts Risk of Metastasis in Pulmonary Neuroendocrine Neoplasms

Abstract: Recently, collagen/integrin genes have shown promise as predictors of metastasis mainly in non-small cell lung cancer and breast cancer. However, it is unknown if these gene expression profiling differ in metastatic potential of pulmonary neuroendocrine neoplasms (PNENs). In this study, we sought to identify differentially expressed collagen/integrin genes in PNENs in order to understand the molecular mechanisms underlying the development of stroma-associated fibrosis for invasion and metastasis. We compared c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Because fibrosis plays a critical role in metastasis [38][39][40] which frequently accompanies recurrence, we compared the key regulators of fibrosis between the NR and R groups. We found that the collagens COL5A3 and COL12A1 and fibronectins 1 (FN1) were significantly increased in the R samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because fibrosis plays a critical role in metastasis [38][39][40] which frequently accompanies recurrence, we compared the key regulators of fibrosis between the NR and R groups. We found that the collagens COL5A3 and COL12A1 and fibronectins 1 (FN1) were significantly increased in the R samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AutoDock, which is open source and widely used, was selected for SBDD and virtual screening to obtain lead compounds with binding potential to the target. Previous studies have shown that drugs targeting multiple receptors may inhibit the development of IPF better than those targeting individual receptors ( Cheng et al, 2019 ; Prieto et al, 2021 ). To evaluate the feasibility of screening drugs against multiple targets, we first analyzed the spatial structural similarity, sequence similarity, and physiological pathway associations of ligand-binding domains in nine receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Specific ECM alterations regulating tissue biochemical and biomechanical properties have been described in NETs [ 40 ], which may imply that several ECM glycoproteins may contribute to the tumorigenesis of NETs. In a recent study, the up-regulation of six fibrogenic genes ( COL5A2 , COL1A2 , COL3A1 , ITGA5 , ITGB1 , and ITGB1 ) in pulmonary neuroendocrine carcinoma and the down-regulation of pulmonary neuroendocrine neoplasms were strongly related to no metastasis and overall survival [ 41 ]. Only one study has shown that the activation of the lysine degradation pathway injures tumor cell proliferation [ 42 ], which is also related to miR-769-5p tumor suppression, as shown in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%